Credit Risk and Disclosure Behavior in the Bank Industry: Evidence From Saudi Arabia - Qadiri, Hind; Alsughayer, Sulaiman (International Journal of Accounting and Financial Reporting, 2021)
This study investigates the extent of credit risk disclosure and the effects of bank-specific attributes on the disclosure level of Saudi listed banks. The study considers the content analysis of 12 Saudi listed banks from 2016 to 2020. A comprehensive credit risk disclosure index is developed, covering seven dimensions to measure the levels of credit risk disclosure. The generalized linear model is used to examine whether bank-specific attributes could explain any differences in disclosure levels among banks. This research provides evidence that although banks have similar regulatory requirements, they differ in their credit risk disclosure. The empirical results indicate that few bank-specific attributes significantly influence the risk disclosure. Bank size and leverage positively affect risk disclosure. Therefore, banks’ asset size is a key factor in all risk disclosure categories. In contrast, the results show that a bank’s age and profitability have no impact on the level of credit risk disclosure. This paper contributes to the risk disclosure literature in Saudi Arabia. Understanding factors that affect the level of credit risk disclosure might help the regulators to formulate strategies and policies, enabling shareholders and investors to make informed decisions.